CORRELATION TYPES OF COMPOUNDS - Hakimova Marguba (TADQIQOTLAR, 2025)
Abstract The study of compound words within the framework of correlation with free word-groups offers a comprehensive understanding of the systemic and productive nature of English word-formation. This article focuses primarily on adjectival-nominal compounds as one of the most productive and semantically motivated categories. By analyzing their structural patterns and their semantic correspondence with syntactic constructions, the article demonstrates how such compound units are formed and function in modern English. The research highlights the role of lexical valency and semantic compatibility between components in the process of compound formation. The analysis is aimed at revealing the mechanisms behind the construction of compound adjectives and understanding their syntactic and semantic roots.